1997
DOI: 10.1044/jslhr.4004.741
|View full text |Cite
|
Sign up to set email alerts
|

Three Accounts of the Grammatical Morpheme Difficulties of English-Speaking Children With Specific Language Impairment

Abstract: Several hypotheses have been offered to explain the grammatical morpheme difficulties observed in the speech of children with specific language impairment. Three of the accounts that could be evaluated in English were the focus of this study: the extended optional infinitive account, the implicit rule deficit account, and the surface account. Preschoolers with specific language impairment, a group of age controls, and a group of younger children matched for mean length of utterance were evaluated in their use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
240
5
7

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(258 citation statements)
references
References 14 publications
4
240
5
7
Order By: Relevance
“…Importantly, though, these errors were only made for irregular verbs. This pattern of past tense marking in language impaired children with autism is uncharacteristic of that in SLI in which bare stem errors are characteristically observed only with regular forms (Leonard et al, 1992;Leonard, Eyer, Bedore & Grela, 1997;Oetting & Horohov, 1997). In sum, the kinds of errors in tense marking of regular verbs made by language impaired children with ASD do not closely resemble the kinds of errors made by children with SLI (cf.…”
Section: Summary and Discussionmentioning
confidence: 69%
“…Importantly, though, these errors were only made for irregular verbs. This pattern of past tense marking in language impaired children with autism is uncharacteristic of that in SLI in which bare stem errors are characteristically observed only with regular forms (Leonard et al, 1992;Leonard, Eyer, Bedore & Grela, 1997;Oetting & Horohov, 1997). In sum, the kinds of errors in tense marking of regular verbs made by language impaired children with ASD do not closely resemble the kinds of errors made by children with SLI (cf.…”
Section: Summary and Discussionmentioning
confidence: 69%
“…Numerous researchers have put forth the hypothesis that the protracted language development exhibited by children with SLI is the result of deficits in basic cognitive and perceptual processes that are essential for learning and producing language as well as for certain other cognitive operations (Ellis Weismer, Evans, and Hesketh (1999), Leonard, Bortolini, Caselli, McGregor, and Sabbadini (1992), Leonard and Eyer (1996), Leonard, Eyer, Bedore, and Grela (1997), Marton and Schwartz (2003), Miller, Kail, Leonard, and Tomblin (2001); and see review in Leonard (1998)). For example, the Generalized Slowing Hypothesis (GSH) holds that because children with SLI have demonstrable limitations in speed of processing, interpreted through reaction time in both linguistic and nonlinguistic tasks when compared with unaffected age-matched children, these limitations slow down their ability to take in linguistic input, store it in memory, and in turn access appropriate structures in language production (Miller et al (2001), Windsor and Huang (1999), Windsor, Milbrath, Carney, and Rakowski (2001); but see Lahey, Edwards, and Munson (2001)).…”
Section: Domain-general and Domain-specific Accounts Of Slimentioning
confidence: 99%
“…All other things are seldom equal, and accordingly, Leonard (1998) put forward a domain-general account of SLI that combines the GSH with a perceptual limitation account, the Surface Hypothesis (SH) (Leonard et al (1992), Leonard and Eyer (1996), Leonard et al (1997)). Building on research showing that children with SLI have limitations compared to unaffected age mates in their abilities to perceive perceptual contrasts differentiated by sounds with brief phonetic duration and display phonological processes such as final consonant and weak syllable deletion more than unaffected age mates, Leonard and his colleagues (Leonard (1998), Leonard et al (1992), Leonard and Eyer (1996), Leonard et al (1997)) hypothesized that grammatical morphemes that are of short duration or otherwise phonologically nonsalient would be more difficult for children with SLI to perceive and encode in a stable representation.…”
Section: Domain-general and Domain-specific Accounts Of Slimentioning
confidence: 99%
“…For example, Tallal and Piercy (13) found that some children with SLI have difficulty reporting the order of pairs of high-and low-frequency sounds when these sounds are brief in duration and presented rapidly. Such a deficit may underlie difficulties in perceiving grammatical forms (e.g., the or is), which are generally brief and unstressed (17).…”
mentioning
confidence: 99%